ASSESSING THE INFLUENCE OF SOIL PROPERTIES ON OPTIMAL PRODUCTION STRUCTURE AT VEGETABLE FARMS - Ivana Janeska Stamenkovska , Aleksandra Martinovska Stojcheska , Mile Markoski , Jaka Zgajnar (CONTRIBUTIONS, Section of Natural, Mathematical and Biotechnical Sciences, MASA, Vol. 40, No. 2, pp. 229–238 (2019), 2019)
The variability in soil properties influences the farm management decisions in reference to the fertilizers’ opti mization strategy and crop productivity. The aim of this research is to assess the influence of chemical soil properties on optimal production plan at vegetable farms in R. Macedonia, utilizing optimization potential of mathematical program ming techniques. The study simulates the economic performance of a typical vegetable farm in four scenarios based on different soil contents of key nutrients; hence four fertiliser management strategies are defined. Main results point to the optimal scenario, where the solution provides highest gross margin, lowest number of enterprises, highest labour en gagement, but relatively modest working capital. Vegetable crops included in the optimal production plan have more need for potassium, nevertheless the nitrogen and phosphorus are also important. The offered options for basic fertiliza tion and additional nutrition can be considered as reasonable and realistic solution that can be applied in practice
Keywords: soil properties; optimal production structure; multi-criteria decision making; vegetable production